2016
DOI: 10.1002/adfm.201600593
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Polymeric Fluorescent Nanoparticles Based on Quadruple Hydrogen Bonds

Abstract: 5483wileyonlinelibrary.com biocompatibility. Accordingly, there has been a surge in the exploitation of CPNs in numerous exciting studies. [ 9 ] Covalent polymers, however, suffer from the need for tedious chemical modifi cation to tune the emission color of their corresponding nanoparticles.Supramolecular polymers, which are formed from low-molecular-weight monomers by noncovalent interactions, provide a promising scaffold for the fabrication of fl uorescent nanoparticles with well fi ne-tuned emission prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 116 publications
(57 citation statements)
references
References 62 publications
(27 reference statements)
1
56
0
Order By: Relevance
“…Likewise, composite crystals of D and a non-TADF analog of A, A′ with a similar absorption spectrum as A manifested no detectable luminescence (Supporting Information Figure S11). This result is consistent with nonradiative relaxation of T 1 of A′ populated by an efficient triplet-to-triplet energy transfer from D. Although tuning emission properties by excitation energy transfer has been investigated extensively, 34,35,[39][40][41][42][43][44][45] to the best of our knowledge, our material is the first example to manifest persistent TADF by using triplet-triplet energy transfer.…”
Section: Resultssupporting
confidence: 84%
“…Likewise, composite crystals of D and a non-TADF analog of A, A′ with a similar absorption spectrum as A manifested no detectable luminescence (Supporting Information Figure S11). This result is consistent with nonradiative relaxation of T 1 of A′ populated by an efficient triplet-to-triplet energy transfer from D. Although tuning emission properties by excitation energy transfer has been investigated extensively, 34,35,[39][40][41][42][43][44][45] to the best of our knowledge, our material is the first example to manifest persistent TADF by using triplet-triplet energy transfer.…”
Section: Resultssupporting
confidence: 84%
“…Here, the water‐dispersible nature makes the aqueous dispersion of the photoswitchable fluorescent LCNPs as green and eco‐friendly inks that are first applied to information encryption technology. Considering accuracy, readability of information, and operation simplicity of the information writing, inkjet printing is particularly appropriate when LCNPs are employed to construct system . The aqueous suspension in which the polymerized LCNPs are dispersed was concentrated by evaporating water at room temperature.…”
mentioning
confidence: 99%
“…S34). It further demonstrated that these POSS-containing 2D nanocrystals functioned as excellent light-harvesting systems ( 28 , 58 ).…”
Section: Resultsmentioning
confidence: 92%